Efficacy and safety of levetiracetam in preventing postoperative seizures in adult patients with brain tumors: a meta-analysis - Zhang, Yongyi; Li, Haoming; Zhang, Bin; Zhang, Junchen; Li, Chengde (Frontiers in Neurology, 2025)
ObjectiveSeizures are one of the most common symptoms in patients with brain tumor. The efficacy of prophylactic antiepileptic agents in reducing postoperative seizures in patients with brain tumor remains disputed. We conducted this meta-analysis to evaluate the efficacy and safety of levetiracetam in preventing seizures in adult patients with brain tumor.Review methodsWe gathered studies comparing the effectiveness of levetiracetam with other antiepileptic drugs in preventing postoperative seizures in individuals with brain tumor from 2008 to 2023. We used the search terms levetiracetam, brain tumor, prevention, and seizures to retrieve relevant studies from the Pubmed, Medline, EMBASE, China National Knowledge Infrastructure, and Wanfang databases. The meta-analysis was conducted using RevMav 5.3 software.ResultsAfter the literature search and screening, nine English-language studies involving a total of 2,433 patients were analyzed. The meta-analysis revealed that levetiracetam had higher efficacy for preventing overall seizures than the control intervention (odds ratio [OR] 0.56, 95% confidence interval [CI] 0.44–0.71, p < 0.00001). Subgroup analyses revealed that the efficacy of levetiracetam was superior to that of sodium valproate (OR 0.53, 95% CI 0.39–0.72, p < 0.0001) and phenytoin sodium (OR 0.35, 95% CI 0.19–0.62, p = 0.0004). No statistically significant difference in the efficacy of early seizure prophylaxis (OR 0.55, 95% CI 0.15–2.04, p = 0.37) was observed. The subgroup analysis revealed that the efficacy of levetiracetam for preventing early seizures was better than that of phenytion sodium (OR 0.13, 95% CI 0.03–0.56, p = 0.006). No statistically significant difference was noted in the preventive efficacy against late seizures (OR 0.75, 95% CI 0.27–2.03, p = 0.57). The incidence of adverse drug reactions was lower in the levetiracetam group than in the control group (OR 0.18, 95% CI 0.05–0.64, p = 0.008). Further subgroup analyses revealed that the incidence of adverse drug reactions in the levetiracetam group was lower than that in the phenytion sodium group (OR 0.06, 95% CI 0.02–0.21, p < 0.001).ConclusionProphylactic levetiracetam decreases the frequency of postoperative seizures, particularly early postoperative seizures, in individuals with brain tumor, with superior effectiveness to phenytion sodium and sodium valproate. In addition, levetiracetam induced only minor adverse effects, with a lower occurrence rate of adverse reactions than phenytion sodium and valproate. Nevertheless, a potential for bias exists. Due to the limited number of high-quality randomized controlled trials included in this meta-analysis, prospective, multicenter, ethnically diverse, high-quality studies on levetiracetam are essential to determine the efficacy of preventive levetiracetam in managing postoperative seizures.Systematic review registrationhttps://inplasy.com/inplasy-2023-6-0091/